L-Valine Fermentation by Brevibacterium flavum Strain NV246 - Huanmin, Liu; Xiangyang, Ge; Weiguo*, Zhang (Asian Journal of Chemistry, 2011)
A L-valine hyper-producer Brevibacterium flavum strain NV246 (a-ABhr, D-glucosehr) was obtained, which could be resistant to high concentration of a-aminobutyric acid (a-AB) or D-glucose. The result indicates that the final L-valine concentration, 20 % glucose added in the culture medium at one time at the beginning of the fermentation process, is much higher than the one adding lower percentage of glucose in the medium at several times during the process. The influence of some alcohols on the L-valine production by strain NV246 was studied. The result indicates N-butyl alcohol and ethylene glycol enhance the production of L-valine.